Influence of Various Types of Chitosan on Biomass and Callus Morpology of Momordica Cochinchinensis in Vitro - Lamante, Nazwa S.; Pagalla, Devi Bunga; Ahmad, Jusna; Kandowangko, Novri Youla; Husain, Indriati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Momordica cochinchinensis is a medicinal, herbs locally known in gorontallo as dumbaya. Tradisionally, this plant has been utilized as both a food of food course a herbal medicine. Due to its rich contains of bioactive compounds, making it a potential candidate for development through plant tissue culture. This study aimed to determine the effects of different chitosan concentrations on the biomass and callus morphology of M. cochinchinensis cultivated in vitro. The experiment was arranged in a non-factorial completey randomized design consisting of three chitosan concentrations: 15 mg L -1, 25 mg L-1, and 35 mg L-1, respectively, as well as a 5000 mg L-1 chitosan stock solution per liter of MS medium. Each treatment consisted of three replicates. The observed parameters included callus fresh weight, dry weight, color, texture, and the percentage of callus formation. Data were analyzed using a one-way ANOVA at a 5% significance level. Since the fresh weight data showed significant differences, it was followed by a Duncan’s Multiple Range Test (DMRT) at the 5% level. The results showed that different chitosan concentrations significantly affected the callus fresh weight (F = 7.932; p = 0.021). the 15 mg L-1 treatment yielded the highest fresh weight, 0.04067 ± 0.0115 g, which was significantly different from the 35 mg L-1 treatment (0.3000 ± 0.0458 g) but not significantly different from the 25 mg L-1 treatment (0.3300 ± 0.0346 g) conversely, chitosan concentration did not significantly affect the culls dry weight (F = 3.519); p = 0.097). all treatmeants resulted in 100% callus formation with white and friable callus morphology. These findings indicate that among the tasted concentrations, 15 mg L-1 of chitosan is the most favorable concentration for demonstrating callus fresh weight accumulation of M. cochinchinensis under in vitro culture conditions.